Shifts of Voter Behavior in the Election of Local Head and Their Impact on the Implementation of Government in Nabire District 2020 – 2022 - Sawaki, Mariana Tresia; Yist, Franciscus Van; Rahmatunnisa, Mudiyati (Universitas Muhammadiyah Ponorogo, 2022)
The purposes of this study (1) are to analyze why the electronic performance reporting of the work unit at the Nabire Regency Secretariat causes the performance of the local government to be unable to meet the real needs of the region; (2) To analyze why the filling of structural positions in the Nabire Regency Secretariat does not prioritize service to the community. The research uses a qualitative approach through the process of finding, understanding, explaining and obtaining an overview. The result is that Electronic Performance Reporting in several Work Units at the Nabire Regency Secretary has not fully referred to the symbolic policy model, and the filling of structural positions in the Nabire Regency Secretariat has not prioritized service to the community because it has not referred to the procedural policy model.